Insight into the phase evolution of a NiMgAl catalyst from the reduction stage to the post-reaction stage during the dry reforming of methane. Issue 44 (18th May 2017) - Bao, Zhenghong; Zhan, Yiqiu; Street, Jason; Xu, Wenqian; To, Filip; Yu, Fei
Abstract : A NiMgAl oxide catalyst was characterized and analyzed using in situ synchrotron XRD during the catalyst reduction, DRM reaction, and post-reaction. Abstract : Herein, phase evolution of a NiMgAl oxide catalyst at the reduction stage was qualitatively analysed and quantitatively determined by employing the continuous changes in its XRD intensity and TPR information. The stable crystallite size of both the active metal and spinel support was responsible for the long stability of the NiMgAl catalyst without carbon deposition during the DRM reaction.